Dependence as A Psychological Problem in The “Tulisan Sastra” Novel by Tenderlova and its Utilization for Recommendations of Novel Text Teaching Materials in High School - Octaviani, Salbina Amalia; Muhtarom, Imam; Herlina, Dewi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study  aims for describing the structure of the novel contained in the Sastra Tulisan Novel work Tenderlova , analyzing psychological figures in the Sastra Tulisan Novel work Tender experience dependence as problem psychology,, describing utilization of Novels in Sastra Tulisan work Tender as recommendation learning teaching materials Indonesian language at high school level . This research uses a qualitative approach with descriptive method. Subject in study This is a literary novel work Tenderlova and objects study This is the structure of the novel is intrinsic elements and psychological figures in the novel Sastra Tulisan. The results of the study show major theme: love and loss, minor theme: broken family after the death of Mr. Suyadi and the death literary figure because accident tragic . The plot or flow used in the Sastra Tulisan Novels channel mixed . Characters and characterization consists of from Andhika Sastra Gautama, Mr. Suyadi, Oktavia Sahara Dewi, Mother, Adhitama Abelvan, Eros Bratadikara Nayaka, Jovan Akhal Raksi, Adinata Aileen Caesar, Adelardo Cetta Early, Kin Dhananjaya, and Jeffry. background place: house, yard front house, campus corridor, park faculty, BK room, Sahara rented house, house sick. background time Morning day, afternoon day, afternoon, evening day, June 2, 2020, at four early days, six days, and two weeks. background socio-cultural simplicity reflected in method life as well as family values ​​in value connection between human. Language that is used very closely with everyday life, reflecting daily conversation with use of words that tend to be relaxed, the language used also contains figures of speech metaphor, figures of speech personification, and figures of speech hyperbola. Angle view in the Sastra Tulisan Novelusing third person all-round know . The mandate contained in the literary writing novel, namely family as a place to learn, appreciate difficulty with being grateful, and don't keep sadness alone.